Silencing Aurora-kinase-A (AURKA) reinforced the sensitivity of diffuse large B-cell lymphoma cells to cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) via suppressing β-Catenin and RAS-extracellular signal-regulated protein kinase (ERK1/2) pathway. Issue 1 (1st January 2021) - Wang, Shaoxiong; Sun, Li
ABSTRACT: The therapeutic effects of standard cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) therapy for prevalent lymphoma diffuse large B-cell lymphoma (DLBC, DLBCL) still require improvement. Cancer-related aurora-kinase-A (AURKA) may work as a target for DLBCL treatment and its effect on CHOP therapy was investigated in the present study. The Gene Expression Profiling Interactive Analysis 2 was applied to analyze AURKA expression in DLBC tumor tissues and normal lymphoid tissues. The DLBCL tissues and normal lymphoid tissues were obtained from the DLBCL patients and healthy volunteers. Clinic data of patients were recorded, and AURKA expression in tissues and cells was detected and analyzed using quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry. After AURKA in DLBCL cells was silenced or overexpressed and treated with CHOP, viability and apoptosis were detected by Cell Counting Kit-8 (CCK-8) assay and flow cytometry. Expressions of AURKA, β-Catenin, phosphorylated (p)-β-Catenin, extracellular signal-regulated protein kinase (ERK1/2), p-ERK1/2 and RAS were detected using qRT-PCR and Western blot. AURKA was highly expressed in DLBCL tissues and cells. Silencing AURKA inhibited AURKA expression and viability, but promoted apoptosis of DLBCL cells. CHOP had no obvious effects on AURKA expression while reducing viability and promoting apoptosis of DLBCL cells. Silencing AURKA enhanced the effects of CHOP on cell apoptosis of DLBCL cells by inhibiting the expressions of RAS and β-Catenin as well as the ratio of p-ERK1/2/ERK1/2 and promoting the ratio of p-β-Catenin/β-Catenin. Silencing AURKA reinforced the therapeutic effects of CHOP on reducing viability and promoting apoptosis of DLBCL cell via repressing β-Catenin and RAS-ERK1/2 pathway.